Factors affecting credit risk in Indonesian Islamic banks - Haryono, Yono; Mohd. Ariffin, Noraini; Hamat, Mustapha (IIUM Press, 2016)
This study uses dynamic panel data methods to examine the factors affecting credit risk in Indonesian Islamic banks. The panel data is collected from 11 full-fledged Islamic banks and 22 Islamic business units (windows) in conventional banks from 2004-2012, taking into account both macroeconomic variables and bank-specific variables. The Generalized Method of Moments (GMM), as proposed by Arellano and Bond (1991), is utilized to estimate the model. The results show that the GDP growth rate and the unemployment rate with a one-year lag have a strong effect on the level of the non-performing financing. Moreover, bank-specific variables such as bank’s diversification and financing structure have a positive effect on the problem financing although its direction is not as expected. It is hoped that the findings could draw attention to factors affecting credit risk in Islamic banks so that credit risk can be properly managed.